Metabolic response of intestinal microbiota to guar gum consumption - Barber, Claudia; Sabater, Carlos; Guarner, Francisco; Margolles, Abelardo; Azpiroz, Fernando (Frontiers in Nutrition, 2023)
Background: Guar gum is is used extensively as thickening agent in food, but it remains uncertain whether and to what extent it is fermented by colonic microbiota and whether it has microbiota modulatory properties. Aim: To determine the metabolic response of intestinal microbiota to guar gum consumption, specifically, the extent of initial fermentation and subsequent adaptation. Methods: Single-centre, single arm, open label, proof-of-concept study testing the effect of guar gum on microbiota metabolism and adaptation. Healthy subjects (n=12) were administered gum guar (8 g/d) for 18 days. Outcomes were measure before, at initial and late administration: a) anal gas evacuations (number/d); b) digestive sensations (daily scales); c) fecal gut microbiota taxonomy and metabolic functions by shotgun sequencing. Results: At initial consumption, guar gum induced a transient increase in anal gas evacuations and digestive sensations; gas evacuation completely reverted upon continous administration, whereas sensations reverted only in part. Guar gum induced moderate changes in human microbiota composition at both taxonomic and functional levels. Positive associations between effects on microbiota (proliferation of Agathobaculum butyriciproducens and Lachnospira pectinoschiza) and hedonic sensations were detected. Conclusion: Guar gum is metabolized by intestinal microbiota, and, upon continuous consumption, induces a selective adaptation of microbial taxonomy and function. These data highlight the potential interest of guar gum for novel prebiotic ingredient formulation.